ANALISA KEBUTUHAN SISTEM PROTEKSI PETIR PADA METERING REGULATING STATION KIOSK PELANGGAN PT PERUSAHAAN GAS NEGARA .TBK SESUAI DENGAN PERATURAN UMUM INSTALASI PENANGKAL PETIR DAN SNI 03-7015-2004 - Siswanto, Eko Haris; Tamaji (Seminar Nasional Ilmu Terapan, 2024)
PT Perusahaan Gas Negara .Tbk (PGN) is a Pertamina Gas Sub-Holding which operates in the field of natural gas transportation. In the distribution process it is necessary to regulate the pressure according to customer needs and measure the volume of use. One of the equipment used to regulate the pressure to customers is metering. Regulating Station Kiosk (MRS Kiosk),to obtain Approval for Eligibility for Operation (PLO) from the Directorate General of Oil and Gas - Ministry of Energy and Mineral Resources, for operational and public safety it is necessary to install a lightning protection system and grounding system, calculating the need for a lightning strike protection system can use standards that already exists, namely the General Regulations for Lightning Distribution Installations (PUIPP) and SNI 03-7015-2004. Based on the data obtained, the MRS Kiosk of PT Bintang Float Glass in Subang City is on a flat plain with a low level of vulnerability to lightning strikes, namely 31 days of thunder per year, and the dimensions of the MRS Kiosk are 10.4 meters long, 6.6 meters wide and 3.65 meters high so that bycalculating with PUIPP standards and SNI 03-7015-2004 the same results are obtained, namely that it does not require a lightning protection system.